Why Variable-Population Social Orderings Cannot Escape the Repugnant Conclusion: Proofs and Implications - Dean Spears; Mark Budolfson (Institute of Labor Economics (IZA), 2019)
The population literature in theoretical economics has long focused on attempts to avoid the repugnant conclusion. We advance the literature by proving that no social ordering in population economics can escape the repugnant conclusion in all instances. As we show, prior results depend on a formal definition of the repugnant conclusion that artificially excludes some repugnant cases. In particular, the literature traditionally formalizes the repugnant conclusion to exclude cases that include an unaffected subpopulation. We relax this normatively irrelevant exclusion, and others. We prove that any candidate social ordering that satisfies either a basic axiom of Aggregation or Non-Aggregation implies some instance of the repugnant conclusion. Therefore, the repugnant conclusion provides no methodological guidance for theory or policymaking, because it cannot discriminate among candidate social orderings. This result is of practical importance because evaluation of important climate or development policies depends on comparing social welfare across populations of differing sizes.
Keywords: J10; J13; J18; D63; 330; population economics; population ethics; repugnant conclusion; RDGU; CLGU; separability